Quality Analysis of Digital Service Virtual Plasa Witel Samarinda Using e-Servqual Method - Syafitri Khotijah; Dharma Widada; Theresia Amelia Pawitra (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
Virtual Plasa is a new digital service from PT. Telkom, released in 2020, with the intention of providing communication services from Telkom concisely. This study aims to determine the quality of service at Virtual Plasa, identify and evaluate the causes of the gap, and recommend improvement. The results show that Virtual Plasa services have a significant level of service quality. Even if the average expectation is higher than the average perception, the difference is modest, and the overall service is good. The Wilcoxon test results show that only two of eighteen attributes have a significant negative value, which is the website has a positive image and follow up on the website as promised. The attribute "Follow up on the website as promised" appears in the IPA diagram's priority quadrant. This attribute's fulfillment gap is caused by information gap (-0.58). Recommendation for this issue involve scheduling management to monitor directly the transactions done, creating a record feature, and asking customers to fill out the feedback section after completing transactions in Virtual Plasa. On the IPA diagram, the attribute "website has a positive image" is found in the low priority quadrant. The recommendation include creating defined guidelines for the Virtual Plasa image.